Design of 12 v dc to 240 v ac inverter for induction motor application - Noor Ishamudin Ismail (School of Electrical System Engineering, University Malaysia Perlis, 2011)
Inverter is an electrical device that converts Direct Current (DC) to Alternating Current (AC). The converted AC can be at any required voltage and frequency with the use of appropriate transformers, switching, and control circuits. In this project, it is an electronic circuit which converts battery voltage into mains voltage, 12 V DC from the battery converted to 240 V AC and will connect to induction motor. Inverters are commonly used to supply AC power from DC sources such as solar panels or batteries. Power inverters, regardless of size, are typically constructed of a DCAC converter. A square wave output will be obtained through the use of a microcontroller and high frequency switching. The microcontroller will be used to digitally drive the transistors on the inverter side of the circuit. This will result in pulses at precise time intervals. The slope and magnitude of the output signal will be exact, as opposed to the unstable signal generated by other power inverters that use analog technology. This power inverter will operate using high frequency switching technology. The harmonics that are produced using high frequency switching will include those near the range of the switching frequency, and those that are of a relatively higher order than the 50 Hz frequency. Future work could be done to further improve efficiency, total harmonic distortion, and size of the power inverter. With these additional improvements, the standard DC/AC power supplies could be raised for induction motor application.